Running performance in Brazilian professional football players during a congested match schedule - Vieira, Luiz H. Palucci [UNESP]; Aquino, Rodrigo; Lago-Peñas, Carlos; Martins, Guilherme H. Munhoz; Puggina, Enrico F.; Barbieri, Fabio A. [UNESP] (Wolters Kluwer, 2018)
The purpose of the study was to examine the influence of playing congested fixtures (2 matches a week) on running performance of Brazilian professional football players, pooled (all performance files regardless players' rotation between games) or individualized data treatment (including only files of athletes' who played pair(s) of noncongested-congested matches which occurred on the same week). Forty participants were observed 1-37 times during 59 official matches over 3 years. Global positioning system devices were used to compute total distance covered, maximal sprinting speed mean speed (VAVERAGE), and high-intensity activities (HIA: ≥15 km·h-1). Independent variables included match status (win, draw, and lose), location (home and away), opponent quality (weak and strong), competitive standard (national and state), team formation (4-4-2 and 4-3-3), and position (defender, midfielder, and forward). Student's t-test, effect sizes (d), and magnitude-based inferences were performed to detect differences between congested and noncongested fixtures for each independent factor. Overall, pooled and individualized data treatment revealed contrasting results. The first showed chances of positive outcomes playing congested matches (possibly to very likely; d = 0.09-0.55), for all variables, as using 4-4-2 and state tournament. Conversely, individualized data analysis revealed that during national leagues (possibly; d = 0.24) or forward position (likely; d = 0.70), the players presented reduced HIA when played congested than noncongested periods (p ≤ 0.05). Using 4-3-3 (d = 0.26) or when draw (d = 0.41), possibly lower HIA was also identified. Coaching staff should be aware of performance oscillations such as detrimental effects on HIA during congested periods.
Keywords: Fixture congestion; Global positioning system; Magnitude-based inferences; Match analysis; Soccer; Work rate